Karakteristik Beton Mutu Tinggi dengan Substitusi Slag Baja dan Slag Nikel Sebagai Agregat Kasar - Komang Saka Suwindu; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study aims to determine the value of compressive strength, split tensile, and flexural strength in high quality concrete with variations in the substitution of steel slag and nickel slag as a substitute for coarse aggregate. Concrete tests performed include compressive strength, split tensile strength, and flexural strength. The research process starts from checking the characteristics of slag, and fine aggregate then mix designs and make test specimens in the form of cylinders of 150 mm x 300 mm as many as 36 pieces and beams of 150 mmx 150 mm x 600 mm as many as 9 pieces. The results showed the substitution of steel slag and nickel slag on compressive strength, split tensile strength, and flexural strength, the greater the percentage of nickel slag, the greater the increase in compressive strength, split tensile strength and flexural strength. Compressive strength value with 20% nickel slag substitution increased 3.347%; and for 30% nickel slag substitution increased by 4.603%. The value of split tensile strength with 20% nickel slag substitution increased by 30.137%; and for 30% nickel slag substitution increased by 46.585%. The value of flexural strength with substitution of 20% nickel slag increased 31.674%; and for 30% nickel slag substitution increased by 66.179%. The relationship between compressive strength and average tensile strength obtained in high quality concrete with nickel slag substitution 0%, 20%, 30% at 28 days is 9.3%. The relationship of compressive strength with the average flexural strength obtained in high quality concrete with nickel slag substitution of 0%, 20%, 30% at 28 days is 0.621 .